Protection of life & progeny: do our mothers have good nutritional knowledge, attitude and practice? - Ikhsan, Liyana Nabihah; Mohd Nasaruddin, Nur Asifa; Othman, Farhana; Abd. Aziz, Karimah Hanim; Ismail, Hamizah (2016)
Background: Balanced and sufficient maternal nutritional intake ensures not only the wellbeing of pregnant mother, fetus and newborn, but also her future health and her three generations. Nutritional inadequacies during pregnancy have been reported and several factors were attributed. Objectives were to measure nutritional knowledge, attitude and practice (KAP) during pregnancy and the relationship with socio-demographic characteristics. Methods: Cross-sectional study was conducted among 320 antenatal and postnatal mothers in Hospital Tengku Ampuan Afzan (HTAA), Pahang, Malaysia from 18th July to 27thAugust 2016. A pre-tested self-constructed, interviewguided questionnaire was used. Independent variables were age, marital status, monthly household income, educational level and ethnicity. Outcomes were nutritional KAP level with median used for the categorization. Relationship between independent variables and outcomes obtained by logistic regression with significance at p<0.05. Results: Sixty-five percent aged from 25 to 34, 84% Malays, 48% from middleincome family, 52% had good nutritional knowledge, 67% with positive attitude and 55% with good practice. Age and educational level were significantly related to knowledge. Only educational level was significantly related to practice. Less than 70% of respondents have good nutritional KAP, reflected by educational level with more than half of them received up to secondary education. Hence, the rights of mothers in getting necessary and adequate education should be fulfilled. Conclusion: Results emphasize on the importance of empowering girls and women with adequate educations and to strengthen the nutritional and health education of our educational system. It is for them to be knowledgeable with good attitude and practicing healthy nutritional lifestyle as they entering reproductive life, maintaining and transferring at least optimum healthy life to their progenies.